Supplementation with degradable intake protein increases low-quality forage utilization and microbial use of recycled urea - Wickersham, T.A.; Cochran, R.C.; Wickersham, E.E.; Gnad, D.P.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A common production practice throughout the United States is to supplement protein to cattle consuming low-quality forage (forage with a crude protein content of less than 7%) in order to improve animal performance (i.e., maintain body condition score and body weight) during the winter. Protein supplementation increases forage utilization (intake and digestion) and cow performance by supplying ruminal microbes with protein that is essential for microbial growth. Increased microbial activity in turn provides sources of both protein and energy to the cow. In addition to the protein that is fed and degraded in the rumen, ruminants have the ability to recycle urea—the same compound found in fertilizer and cattle feed—to the rumen, where microbes can use the urea to fulfill a portion of their nitrogen requirement. Although nutritionists know that recycling occurs, we have inadequate data to describe this process and, subsequently, the contribution from recycled urea is not adequately included in our present cattle feeding systems. Previous research at Kansas State University has clearly demonstrated that the greatest response to supplemental protein occurs when the supplemental protein is highly degraded within the rumen, as the degradable fraction of protein is directly available to ruminal microbes. The current project’s objective was to measure how much recycled urea is used to meet the microbial nitrogen requirement when increasing amounts of degradable intake protein were provided to steers consuming low-quality forage. Researchers hoped to generate data useful in refining supplementation recommendations for cattle consuming low-quality forage.
Keywords: Beef; Cattle; Forage; Microbial